Anatomical study on variable disposition of structures in the renal hilum - Dawani, Pooja; Mehta, Vandana; Kaur, Amandeep (International Journal of Research in Medical Sciences, 2021)
Background: The hilum is a deep vertical fissure present anteromedially in the kidney, and contains renal vessels and pelvis. Due to advancements in imaging techniques; nephron sparing surgeries like laparoscopic partial nephrectomy have become more common. In these procedures, only specific branch of renal artery, and tributary of renal vein are ligated in the renal hilum. This requires adequate skill of the surgeon as the structures are crowded in the renal hilum. The knowledge of arrangement of renal hilar structures is also important for radiologists to correctly interpret renal angiograms and other radiological scans. Methods: The present study was conducted in the department of anatomy, Vardhman Mahavir medical college, New Delhi on 64 kidneys derived from embalmed human cadavers. The renal hilum was dissected and the sequence of structures from anterior to posterior direction was noted. Results: The kidneys were classified in 6 patterns, with the classical pattern (renal vein, artery and pelvis from anterior to posterior) observed in 37.5% cases only. Remaining 62.5% cases exhibited variations, of which the pattern 2 (V-A1-P-A2) was seen in maximum cases (26.5%). Conclusions: The classical pattern described in anatomical textbooks is not the only pattern of arrangement of renal hilar structures. Instead, variant patterns are commonly encountered. The present study attempts to elucidate the variant anatomy of the renal hilar region to help radiologists and surgeons in proper diagnosis and treatment.